FRI0216 Does ultrasonography guidance increase the yield of temporal artery biopsy in patients with giant cell arteritis? Results from a single-blinded randomized study. (23rd January 2014) - Germanò, G.; Possemato, N.; Pipitone, N.; Cimino, L.; Boiardi, L.; Bajocchi, G.; Macchioni, P.; Salvarani, C.
Abstract : Background: Temporal artery biopsy (TAB) is the gold standard to diagnose giant cell arteritis (GCA), but is negative in approximately 20% of patients Objectives: The study aimed to establish whether Color-doppler-ultrasonography (CDU)-guided TAB might provide a greater yield compared to standard TAB technique in patients with GCA Methods: We enrolled 100 consecutive patients suspected of having GCA from September 2009 through December 2011. The average age of patients was 74 years. At randomization mean values of ESR were 54 mm/1st hour, mean CRP were 6 mg/dl (n.v. <0.5). Two patients were excluded because biopsy showed no evidence of artery. 44 out of 98 patients were taking mean dose of 17.4 mg of prednisone daily for more than 2 weeks. Patients were randomized to undergoing US-guided TAB (group 1), or to undergoing TAB performed according to conventional technique (group 2). Patients randomized to group 1 were 47; those to group 2 were 51. All patients were evaluated by physical examination of the temporal arteries (PETA), CDU and TAB. CDU was carried out by a physician who was blinded to the clinical data of the patients. CDU was performed using an ESAOTE MyLab 70 device fitted with a LA435 probe set for examination of the temporal arteries. The common trunk and the main branches of the temporal arteries were screened in a longitudinal and transverse plane along the entire vessel course. In patients from group 1 the ultrasonographist marked the segment of the temporal artery which showed the largest halo if present. In patients from group 1 the TAB was performed in the segment marked by the ultrasonographist, while in patients from group 2 was carried in according to standard procedure. PETA was performed before CDU. PETA was considered positive in the presence of tenderness or decreased or absent pulse of the temporal arteries. Chi square test was used for statistical analysis. Results: TAB was positive in 33/98 (33.7%) patients, including 17/47 (36.2%) in group 1 and 15/51 (29.4%) in group 2. The difference of TAB positivity between group 1 and 2 was not significant. In total, the halo was detected in 42 (42.9%) patients, 25 (53.2%) in group 1 and 15 (29.4%) in group 2.In the group 1, the frequency of positive biopsy in patients with US evidence of halo was 68% (17/25), while in the group 2 the biopsy was positive in 15 of the overall 51 patients (29.4%). The difference was statistically significant (p=0.0489; OR: 2.31; 95% CI: 0.1-5.3). Conclusions: Halo-guided TAB was associated with a significantly greater probability of being positive. However, the frequency of TAB-positive patients was similar regardless of whether TAB was performed under CDU guidance or not. Disclosure of Interest: None Declared